Tin‐Based Chiral Perovskites with Second‐Order Nonlinear Optical Properties. Issue 11 (12th September 2021) - Zhao, Liangliang; Han, Xiao; Zheng, Yongshen; Yu, Mei-Hui; Xu, Jialiang
Abstract : Metal halide perovskites have attracted extensive attention as the most favorable candidate for nonlinear optical (NLO) effects, due to their superior infrared transparency, flexible structures, and high laser‐induced damage thresholds. Among the perovskite branches, the lead‐based perovskites dominate in virtue of their fascinating optoelectronic properties. However, the ambient instability and toxicity of lead impede their practical applications. Herein, a new class of air‐stable and lead‐free zero‐dimension chiral perovskites manifesting efficient second‐order NLO response is reported. Interestingly, the tin‐based perovskites demonstrate double‐step reversible phase transitions with an acentric space group P 21 at room temperature, whereas their racemic counterparts undergo a distinct one‐step phase transition crystallizing in centric space group P 21 / c . These findings reveal an executable approach to designing multifunctional lead‐free perovskite‐type switchable materials with second harmonic generation (SHG) properties. Abstract : Lead‐free chiral perovskite‐type semiconductors are constructed, demonstrating efficient second‐order nonlinear optical (NLO) response as well as multi‐step phase transition properties. The remarkable air‐stability, environmental friendliness, and high laser‐damaged thresholds enable them as potential candidates for future commercialized NLO device applications.